Valuing Breastfeeding: Health Care Professionals’ Experiences of Delivering a Conditional Cash Transfer Scheme for Breastfeeding in Areas With Low Breastfeeding Rates - Barbara Whelan; Clare Relton; Maxine Johnson; Mark Strong; Kate J. Thomas; Darren Umney; Mary Renfrew (SAGE Open, 2018)
Alongside a randomized controlled trial testing the effectiveness of offering a cash transfer scheme (shopping vouchers) to mothers in areas with low breastfeeding rates, qualitative interviews were conducted with health care professionals delivering the scheme to explore their experiences. Health care professionals ( n = 34; mainly midwives and health visitors) were interviewed in depth. Transcripts from recorded interviews were analyzed using a Framework Analysis approach. There was widespread acceptance of the scheme by health care professionals, with prior concerns regarding bribery and coercion being quickly allayed. Health care professionals reported that the scheme fitted in well with their routine ways of promoting and endorsing breastfeeding. They described their experiences of women’s positive reaction toward the scheme and how the scheme encouraged breastfeeding and gave breastfeeding higher value. Health care professionals reported that the incentives helped them engage women and promote and support breastfeeding in areas with low breastfeeding rates.